Lychee Seed as a Potential Hypoglycemic Agent, and Exploration of its Underlying Mechanisms - Zhang, Yuehong; Jin, De; An, Xuedong; Duan, Liyun; Duan, Yingying; Lian, Fengmei (Frontiers in Pharmacology, 2021)
Food is people’s primal want. Reasonable diet and healthy food not merely provide nutrients for human growth but also contribute to disease prevention and treatment. While following an unhealthy diet can lead to increased risk of many diseases, especially metabolic disorders, such as diabetes. Nature is enriched with different food sources, and it seems that purely natural products are more in line with the current concept of health, which enhance the formation of the notion that ‘Food/Diet Supplements from Natural Sources as Medicine’. As a delicious fruit, the medicinal value such as anticancer, antibacterial, antioxidation, and antiglycating properties of lychee has been excavated. Lychee (Litchi in Chinese) is a subtropical fruit plant belonging to the family Sapindaceae. It has been widely cultivated in warm climates worldwide, particularly in China, for thousands of years. In recent years, various phytochemical components such as quercetin, procyanidin A2, and (2R)-Naringenin-7-O-(3-O-αL-rhamnopyranosyl-β-D-glucopyranoside) have been identified in lychee seed, which may lend lychee seed as a relatively safe and inexpensive adjuvant treatment for diabetes and diabetic complications. In fact, accumulating evidence has shown that lychee seed, lychee seed extracts, and related compounds have promising antihyperglycemic activities, including improving insulin resistance, antiinflammatory effect, lipid regulation, neuroprotection, antineurotoxic effect, and renoprotection effect. In this review, we summarized publications on antiglycemic effects and mechanisms of lychee seed, lychee seed extracts, and related compounds, which included their efficacies as a cure for diabetes and diabetic complications in cells, animals, and humans, attempting to obtain robust evidence basis for clinical application and value of lychee seed.